Hubungan Sistem Sosialisasi Prosedur Dengan Kualitas Pelayanan Pemanduan Lalu Lintas Penerbangan di Divisi Jakarta Area Control Center (ACC) - Muhammad Caesar Akbar (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
This study aims to determine the relationship between the procedure socialization system and the quality of flight traffic guidance services at the Jakarta Area Control Center (ACC) Division. The variables studied were the quality of flight traffic guidance service as the dependent variable and the socialization procedure system as the independent variable. The research method used is correlational research method with field research in the form of questionnaire data collection techniques and interviews as well as library research. The research sample was taken by random sampling technique, which is taking several members of the population randomly as a sample. The research object is directed at the Jakarta Area Control Center Division flight traffic guide. The data is in the form of answers to questionnaires and the requirements for data analysis tests are carried out in the form of normality tests, as well as data analysis tests, namely correlation and simple regression tests. The coefficients obtained were tested for significance. Based on the questionnaire, it was concluded that the procedure socialization system with a score of 2245 and the quality of flight traffic guidance services with a score of 2230 were in the poor category. The results of this study indicate a significant relationship between the procedure socialization system and the quality of flight traffic guidance services. The correlation coefficient of the socialization system with the quality of flight traffic guidance services is 0.680. The coefficient value of 6.738 indicates that an increase in the socialization procedure system by 1 unit will lead to an increase in the quality of flight traffic guidance services by 6,738.Therefore, to maintain and improve the quality of flight traffic guidance services in the Jakarta Area Control Center (ACC) Division it is necessary factors of the existing procedure socialization system